Death‐associated protein kinase 1 (DAPK1) controls CD8+ T cell activation, trafficking, and antitumor activity. Issue 1 (13th November 2020) - Wei, Zhengping; Du, Qiuyang; Li, Pingfei; Liu, Huicheng; Xia, Minghui; Chen, Yufei; Bi, Guoyu; Tang, Zhao‐Hui; Cheng, Xiang; Lu, Youming; He, Ran; Laurence, Arian; et al.
Abstract: Appropriate migration of cytotoxic T effector cells into the tumors is crucial for their antitumor function. Despite the controversial role of PI3K‐Akt in CD8 + T cell mTORC1 activation, a link between Akt‐mTORC1 signaling and CD8 + trafficking has been demonstrated. We have recently discovered that TCR‐induced calcineurin activates DAPK1, which interacts with TSC2 via its death domain and phosphorylates TSC2 via its kinase domain to mediate mTORC1 activation in CD8 + T cells. However, whether DAPK1 regulates CD8 + trafficking into tumors remains unclear. Here, using pharmacological inhibitor and genetic approaches, we found that like rapamycin, inhibition of DAPK1 activity led to enhanced expression of the homing receptors CD62L and CCR7. Deletion of either kinase domain or death domain in the T cell compartment reduced the T cell activation and maintained the expression of CD62L and CCR7. DAPK1‐DD‐deficient mice were more susceptible to tumor growth and deficiency of DAPK1 activity significantly reduced the migratory ability of CD8 + into the tumors. These data revealed a crucial role of DAPK1‐mTORC1 in mediating CD8 + trafficking and antitumor function.